2022
DOI: 10.1093/nar/gkac855
|View full text |Cite
|
Sign up to set email alerts
|

Non-canonical Staphylococcus aureus pathogenicity island repression

Abstract: Mobile genetic elements control their life cycles by the expression of a master repressor, whose function must be disabled to allow the spread of these elements in nature. Here, we describe an unprecedented repression-derepression mechanism involved in the transfer of Staphylococcus aureus pathogenicity islands (SaPIs). Contrary to the classical phage and SaPI repressors, which are dimers, the SaPI1 repressor StlSaPI1 presents a unique tetrameric conformation never seen before. Importantly, not just one but tw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…This dramatic difference between the two observed affinities can be explained if we consider the role of Sa-Stl dimerization in dUTPase binding. It has been shown that Sa-Stl binds to dUTPases as a monomer, while it forms dimers otherwise 12 15 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This dramatic difference between the two observed affinities can be explained if we consider the role of Sa-Stl dimerization in dUTPase binding. It has been shown that Sa-Stl binds to dUTPases as a monomer, while it forms dimers otherwise 12 15 .…”
Section: Resultsmentioning
confidence: 99%
“…If derepression is not caused by proteolysis, then antirepressors function by either (i) directly disturbing the DNA binding segment of the repressor protein like in the case of the Sri antirepressor protein of the 80α phage and the Stl repressor of SaPI1 Staphylococcus aureus pathogenicity island 12 or (ii) perturbing the oligomerization of the repressor as in the case of several phage dUTPases and SaPIbov1 Stl (Sa-Stl) 2 , 13 15 . In such cases the antirepressor-repressor interaction has to be stronger than the protein–protein interactions on the oligomer interface.…”
Section: Introductionmentioning
confidence: 99%
“…The SaPI and PICI are mobilized by helper phage [25, 28, 29, 48, 53]. In addition, they are all characterized as having a bidirectional promoter involved in transcription repression [25, 29, 48, 51, 54]. The original discovery and description of SaPI was that they encoded toxin genes.…”
Section: Resultsmentioning
confidence: 99%
“…For example, for the well-studied Staphylococcus aureus pathogenicity islands (SaPIs)the HAE itself encodes a master repressor (in this case, Stl) that keeps the SaPI in the prophage-like state. Stl-mediated repression is counteracted by Stl complexing with specific phage antirepressors that disrupt the formation of Stl-DNA complex [84,85].…”
Section: Discussionmentioning
confidence: 99%
“…For example, for the well-studied Staphylococcus aureu s pathogenicity islands (SaPIs) – the HAE itself encodes a master repressor (in this case, Stl) that keeps the SaPI in the prophage-like state [84]. Stl-mediated repression is counteracted by Stl complexing with specific phage antirepressors that disrupt the formation of Stl-DNA complex [85,86]. Based on our data, we hypothesize that H-NS is silencing the majority of the PLE and thus not relying on a PLE-encoded master repressor, but still requiring a phage-encoded protein to relieve the repression by H-NS and TsrA (possibly through induction of some transcriptional activator that remains to be identified).…”
Section: Discussionmentioning
confidence: 99%